Discourse on Universal Religious Values: A Contemporary Paradigm from an Islamic Transitive Perspective - Ansari Yamamah (Journal of Al-Tamaddun, 2022)
This study discusses the reconceptualization of al-ḍarūriyyah al-khamsah in a transitive Islamic perspective. In formulation of al-ḍarūriyyah al-khamsah has not been explained who is most responsible for the efforts to maintain and protect the al-ḍarūriyyah al-khams? Is each individual? Or a certain authority in a society such as the government of a country? Likewise, is the related issue only limited to maintenance without formulating a fulfillment question?. This research is a library research whose data is extracted from written sources. The research approach used is a transitive Islamic approach that emphasizes the universality aspect of Islam and seeks to connect benefit to the reality of human life. This paper proposes the concept of al-ḍarūriyyah al-khamsah with several developments, namely protecting life (hifz al-hayat), protecting love (hifz al-Mahabbah), protecting loyalty (hifz al-wafa’), protecting dignity (hifz al-‘aradh) and protecting welfare (hifz al-Syu’un al-Ijtima’iyah).